ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP KORBAN PEMERKOSAAN YANG MELAKUKAN ABORSI - Salsabila, Dinda Anisa; Ekaputra, Mohammad; Rumondang Siagian, Putri (Penerbit Lafadz Jaya, 2026)
Rape victims are those who experience serious violations of human rights, both physically and psychologically. Pregnancy resulting from rape often causes ongoing suffering for the victim, so that in certain conditions the victim chooses to have an abortion. To find out and analyze the legal regulations related to the legalization of abortion for rape victims in Indonesia. To find out and analyze the form of criminal legal protection for rape victims who have abortions. To find out and analyze the criminal liability of the perpetrator of abortion by rape victims in criminal law. The research method used is normative juridical with a statutory and conceptual approach, through a study of laws, regulations related to reproductive health, and human rights principles. The results of the study show that Indonesian law basically prohibits the practice of abortion, but provides limited exceptions for rape victims under certain conditions. However, the legal protection provided is not fully optimal due to normative obstacles, law enforcement officers, and social stigma against victims. Therefore, it is necessary to emphasize regulations and a victim-oriented legal approach to ensure certainty, justice, and legal protection for rape victims. The emergence of the abortion problem in Indonesia needs attention from various parties who provide alternative solutions. Moral and religious conflicts are the biggest issues that continue to complicate policy agreements to address abortion.